Surgical treatment of lung cancer in patients with coronary artery surgery - A. V. Reshetov; A. V. Elkin; G. V. Nikolaev; S. S. Stepanov (Вестник хирургии имени И.И. Грекова)
The objective was to improve the surgical treatment tactics in patients with non-small cell lung cancer (NSCLC) and coronary heart disease (CHD), requiring myocardial revascularization.Methods and materials. Two groups consisting of 24 patients operated on for NSCLC were examined. In one group, operations for NSCLC were performed in the second stage after coronary artery bypass grafting (CABG). Survival rates in both groups and factors influencing them were evaluated.Results. The number of postoperative complications in both groups was comparable: 20.8 % in patients with CABG and 16.6 % in the group operated only for NSCLC. Indicators of relapse-free and overall survival did not differ significantly from each other (p=0.90 and p=0.95). Only the stage of the disease (p=0.009) and the implementation of complex cancer treatment in case of its necessity (p=0.035) had a reliably impact on the long-term results of the operation. The first stage of myocardial revascularization surgery did not affect the results of treatment (p=0.94), as well as the age of patients, the volume of performed surgery, the morphological picture of the tumor.Conclusion. The staging approach to the treatment of patients with NSCLC and critical forms of CHD requiring myocardial revascularization is reliable, convenient and does not affect the long-term results of treatment.